Belajar Menabung Sejak Dini: Peningkatan Literasi Keuangan Siswa Sekolah Dasar Melalui Sosialisasi Menabung Oleh Mahasiswa Universitas Borneo Tarakan - Hidayat, Nurul; Ridwan, Ahmad; Ratnasari, Ratnasari; Anzirah, Eny; Kurniawan Purnama, Gidion (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
Saving is a good habit that should be introduced from an early age, especially during elementary school years. This activity aimed to help students understand the importance of managing money from a young age through a financial literacy campaign conducted by students of Universitas Borneo Tarakan. In this program, the university students provided explanations, educational games, and practical examples of simple saving methods that were easy for children to grasp. The socialization was carried out with third-grade students at Elementary School 006 Tarakan. The results showed that students gained a better understanding of the benefits of saving and became more motivated to set aside their pocket money. This activity also received positive support from teachers and parents. It can be concluded that the involvement of university students in financial education can help raise awareness and foster saving habits among children from an early age.